System Xc− inhibition blocks bone marrow-multiple myeloma exosomal crosstalk, thereby countering bortezomib resistance. (1st June 2022) - Wang, Fang; Oudaert, Inge; Tu, Chenggong; Maes, Anke; Van der Vreken, Arne; Vlummens, Philip; De Bruyne, Elke; De Veirman, Kim; Wang, Yanmeng; Fan, Rong; Massie, Ann; Vanderkerken, Karin; et al.
Abstract: Multiple myeloma (MM) cells derive proliferative signals from the bone marrow (BM) microenvironment via exosomal crosstalk. Therapeutic strategies targeting this crosstalk are still lacking. Bortezomib resistance in MM cells is linked to elevated expression of xCT (the subunit of system Xc − ). Extracellular glutamate released by system Xc − can bind to glutamate metabotropic receptor (GRM) 3, thereby upregulating Rab27-dependent vesicular trafficking. Since Rab27 is also involved in exosome biogenesis, we aimed to investigate the role of system Xc − in exosomal communication between BM stromal cells (BMSCs) and MM cells. We observed that expression of xCT and GRMs was increased after bortezomib treatment in both BMSCs and MM cells. Secretion of glutamate and exosomes was simultaneously enhanced which could be countered by inhibition of system Xc − or GRMs. Moreover, glutamate supplementation increased exosome secretion by increasing expression of Alix, TSG101, Rab27a/b and VAMP7. Importantly, the system Xc − inhibitor sulfasalazine reduced BMSC-induced resistance to bortezomib in MM cells in vitro and enhanced its anti-MM effects in vivo . These findings suggest that system Xc − plays an important role within the BM and could be a potential target in MM. Highlights: Both BMSCs and MM cells have increased expression of xCT and GRMs after treatment with bortezomib. System Xc − mediated glutamate release contributes to exosome secretion through GRM binding and downstream signaling. Inhibiting System Xc − reduced BMSC-induced drug resistance to bortezomib in MM cells by reducing exosome secretion.